First, expand the terms in parenthesis by multiplying the by the term outside their respective parenthesis:
2
(
3
x
−
1
)
+
2
(
4
x
+
5
)
=
8
(
2
×
3
x
)
−
(
2
×
1
)
+
(
2
×
4
x
)
+
(
2
×
5
)
=
8
6
x
−
2
+
8
x
+
10
=
8
Next, group and combine like terms:
6
x
+
8
x
−
2
+
10
=
8
14
x
+
8
=
8
Next, subtract
8
from each side of the equation to isolate the
x
term while keeping the equation balanced:
14
x
+
8
−
8
=
8
−
8
14
x
+
0
=
0
14
x
=
0
Now we can divide each side of the equation by
14
to solve for
x
while keeping the equation balanced:
14
x
14
=
0
14
14
x
14
=
0
x
=
0